P134 Effects of post-thawing transport and donor mare age on pregnancy outcomes of vitrified IVP equine embryos produced in a commercial ICSI laboratory - P. Arrondo Navarrete; S.A. Stampfli; J. Sieber; A. Ferrante; A. Ballester; M.B. Rodriguez (Journal of Equine Veterinary Science, 2026)

Serum concentrations of selenium, selenium species and metals in children newly diagnosed with leukemia: a hospital-based case-control study - Marco Vinceti; Teresa Urbano; Bernhard Michalke; Lauren A. Wise; Maria Caterina Putti; Eloise Pulvirenti; Claudia Favara; Silvia Di Federico; Federico Zagnoli; Giorgia Adani; Annadiletta Donà; Roberta Patti; et al. (Environmental Research, 2026)

Correction: Affinity Capture Elution Coupled with Cell-based Cyclic Adenosine Monophosphate Assay as a Platform Method for Detection of Neutralizing Antibodies to Incretin Molecules - Nichole A. Reynolds; Yan Q. Chen; Richard E. Higgs; Boris Calderon; Jeff W. Cramer; Nicoletta Bivi; Michael E. Hodsdon; Heather A. Bullock; Travis E. Shockley; Victoria L. Peek; Justin K. Mack; Deven Lemen; et al. (The AAPS Journal, 2026)

Effects of an optimal defaults grocery shopping intervention on household grocery purchases of families with young children - Stephanie Anzman-Frasca; Juliana Goldsmith; Adrianna Calabro; Karlie Gambino; Leonard H. Epstein; Lucia A. Leone; Brianna Wallenhorst; Gregory E. Wilding; Mackenzie J. Ferrante (Appetite, 2026)

Affinity Capture Elution Coupled with Cell-based Cyclic Adenosine Monophosphate Assay as a Platform Method for Detection of Neutralizing Antibodies to Incretin Molecules - Nichole A. Reynolds; Yan Q. Chen; Richard E. Higgs; Boris Calderon; Jeff W. Cramer; Nicoletta Bivi; Michael E. Hodsdon; Heather A. Bullock; Travis E. Shockley; Victoria L. Peek; Justin K. Mack; Deven Lemen; et al. (The AAPS Journal, 2025)

P18-20 Building Bridges in Tobacco Harm Reduction: A Global Interlaboratory Initiative for Standardized Smoke and Aerosol Exposure Assessment - M. Caruso; R. Emma; P. Zuccarello; S. Rust; G. Carota; K. Poulas; F. Zadjali; A. Sun; V. Volarevic; R. Lesmana; M. Tobi; K. Mesiakaris; et al. (Toxicology Letters, 2025)

A Phase-Appropriate Risk Assessment Strategy in Support of the Safety of Peptide and Oligonucleotide-Related Impurities - Brian W. Pack; Robert W. Siegel; Paul D. Cornwell; Andrea Ferrante; Douglas A. Roepke; Michael E. Hodsdon; Laurent Malherbe; Mark A. Carfagna (The AAPS Journal, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Non-dioxin-like polychlorinated biphenyls (PCB 101, 153, and 180) and adipocyte lipid dysfunctions: Involvement of glycerol and role of aquaglyceroporins in mature 3T3-L1 cells - F. Del Piano; A. Monnolo; A. Lama; C. Pirozzi; F. Comella; S. Melini; C. Naccari; A. Pelagalli; R. Meli; M.C. Ferrante (Toxicology, 2025)

BeyondⓇ extender in donkey semen: evaluation at 5 °C and 17 °C over 7 days - M. Caldevilla; D. Neild; A. Ferrante; I. Cáceres Monie; C. Arraztoa; J. Plaza; J. Otero; M. Gambarotta; M. Miragaya (Journal of Equine Veterinary Science, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Caregivers’ Thoughts and Questions Related to the Complementary Feeding Period - Mackenzie J. Ferrante; Catherine A. Forestell; Kameron J. Moding; Susan L. Johnson (Journal of Nutrition Education and Behavior, 2024)

Indoor quality-oriented approach for the performance evaluation of building retrofit with façade transformation: Case study of student dormitory in Mediterranean climate - A. Gigante; D. Papadaki; C. Mazzoli; V. Ntouros; R.F. De Masi; M.-N. Assimakopoulos; Annarita Ferrante (Energy and Buildings, 2024)

Optimal Defaults in Online Grocery Shopping: A Secondary Analysis to Explore Impacts in Multiresident Households and Families - Mackenzie J. Ferrante; Lily McGovern; Leonard H. Epstein; Kelseanna Hollis-Hansen; Lucia A. Leone; Stephanie Anzman-Frasca (Journal of Nutrition Education and Behavior, 2024)

Yield response to frost in a set of historic wheat varieties - Ariel Ferrante; C. Mariano Cossani; Jason A. Able; Victor O. Sadras (Field Crops Research, 2024)

P17-17: Polystyrene microplastic affects the hepatic antioxidant and detoxifying systems in subchronically exposed gilthead seabream (Sparus aurata) - F. Del Piano; A. Lama; R. Mercogliano; B. Carney Almroth; M.C. Ferrante (Toxicology Letters, 2023)

Evaluation of equine semen frozen in extenders free of animal proteins - Mariana L Caldevilla; Alejandro A Ferrante; Camila Tossici; Julieta C Otero; Mariana C Gambarotta; Claudia C Arraztoa; Marcelo H Miragaya; Deborah M Neild (Journal of Equine Veterinary Science, 2023)

Comparison of different cryoprotectants for freezing donkey jack (Equus asinus) semen - Santiago L Bruno; Deborah M Neild; Jessica P Plaza; Alejandro A Ferrante; María I Carretero; Gustavo EA Olivieri; Carolina P Bianchi; Marcelo H Miragaya (Journal of Equine Veterinary Science, 2023)

User-Centered Development and Patient Acceptability Testing of a Health-Coaching Intervention to Enhance Cancer Survivorship Follow-up in Primary Care - Denalee M. O’Malley; Stacy N. Davis; Rahwana Amare; Bianca Sanabria; Brittany Sullivan; Katie A. Devine; Jeanne M. Ferrante; Patricia A. Findley; Suzanne M. Miller; Shawna V. Hudson (Journal of Cancer Education, 2022)

Development of vascular disease models to explore disease causation and pathomechanisms of rare vascular diseases - Rebecca L. Harper; Elisa A. Ferrante; Manfred Boehm (Seminars in Immunopathology, 2022)

A novel morphological phenotype does not ensure reduced biotic resistance on an oceanic island - M. Ferrante; R. Nunes; L. Lamelas-López; G. L. Lövei; P. A. V. Borges (Biological Invasions, 2022)

Genome-wide SNP analysis of three moose subspecies at the southern range limit in the contiguous United States - Jason A. Ferrante; Chase H. Smith; Laura M. Thompson; Margaret E. Hunter (Conservation Genetics, 2022)
Genome-wide evaluations of genetic diversity and population structure are important for informing management and conservation of trailing-edge populations. North American moose ( Alces alces ) are declining along portions of the southern edge of their range due to disease, species interactions, and marginal habitat, all of which may be exacerbated by climate change. We employed a genotyping by sequencing (GBS) approach in an effort to collect baseline information on the genetic variation of moose inhabiting the species’ southern range periphery in the contiguous United States. We identified 1920 single nucleotide polymorphisms (SNPs) from 155 moose representing three subspecies from five states: A. a. americana (New Hampshire), A. a. andersoni (Minnesota), and A. a. shirasi (Idaho, Montana, and Wyoming). Molecular analyses supported three geographically isolated clusters, congruent with currently recognized subspecies. Additionally, while moderately low genetic diversity was observed, there was little evidence of inbreeding. Results also indicated > 20% shared ancestry proportions between A. a. shirasi samples from northern Montana and A. a. andersoni samples from Minnesota, indicating a putative hybrid zone warranting further investigation. GBS has proven to be a simple and effective method for genome-wide SNP discovery in moose and provides robust data for informing herd management and conservation priorities. With increasing disease, predation, and climate related pressure on range edge moose populations in the United States, the use of SNP data to identify gene flow between subspecies may prove a powerful tool for moose management and recovery, particularly if hybrid moose are more able to adapt.

Lipidomics reveals specific lipid molecules associated with cold stress syndrome in the Florida manatee (Trichechus manatus latirostris) - Emily K. Griffin; Kaylie Anne Costa; Juan J. Aristizabal-Henao; Michael P. Napolitano; Margaret E. Hunter; Jason A. Ferrante; John A. Bowden (Marine Biology, 2021)

A Collaborative European Approach to Accelerating Translational Marine Science - Philip Brennecke; Maria I. Ferrante; Ian A. Johnston; David Smith (Journal of Marine Science and Engineering, 2018)
Marine environments account for over 90% of the biosphere and hold tremendous potential for biotechnological applications and drug discovery. To fully exploit this potential and develop interesting discoveries into useful molecular tools and successful products, a multidisciplinary approach is indispensable. Here, we introduce the European Marine Biological Research Infrastructure Cluster (EMBRIC), a novel collaborative initiative that aims to facilitate translational marine science and remove existing bottlenecks that are currently impeding blue innovation. In the context of this initiative, pilot projects have been designed to test the functionality of the cluster focusing on two specific sectors of marine biotechnology: (i) the discovery and exploitation of marine natural products and (ii) the marker-assisted selection of desirable traits in aquaculture. EMBRIC brings together the expertise of six European Research Infrastructures on accessing the potential of marine organisms, specifically on the 99% of bacteria yet to be grown in culture, the microalgae, finfish, and shellfish. It improves the throughput and efficiency of workflows for discovery of novel marine products and facilitates projects that require an interdisciplinary approach. The objective is to develop coherent chains of high quality services for access to biological, analytical, and data resources by deploying common underpinning technologies and practices. The connection of academic science with industry is being strengthened by engaging companies, as well as geographically separated public and private-sector communities in the domain of marine biotechnology, and by federating technology transfer services amongst the players involved.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Emended description of Pseudomonas syringae pv. avellanae, causal agent of European hazelnut (Corylus avellana L.) bacterial canker and decline - M. Scortichini; P. Ferrante; L. Cozzolino; A. Zoina (European Journal of Plant Pathology, 2016)

Agrobacterium tumefaciens-mediated transformation of axillary bud callus of Hibiscus rosa-sinensis L. ‘Ruby’ and regeneration of transgenic plants - Alice Trivellini; Antonio Ferrante; Donald A. Hunter; Ranjith Pathirana (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Effects of Pseudomonas fluorescens Seed Bioinoculation on Heavy Metal Accumulation for Mirabilis jalapa Phytoextraction in Smelter-Contaminated Soil - M. Petriccione; D. Di Patre; P. Ferrante; S. Papa; G. Bartoli; A. Fioretto; M. Scortichini (Water, Air, & Soil Pollution, 2013)

The interactions of age, sex, body mass index, genetics, and steroid weight-based doses on tacrolimus dosing requirement after adult kidney transplantation - P. Stratta; M. Quaglia; T. Cena; R. Antoniotti; R. Fenoglio; A. Menegotto; D. Ferrante; A. Genazzani; S. Terrazzino; C. Magnani (European Journal of Clinical Pharmacology, 2012)

Cadmium Accumulation and Antioxidant Responses in Sparus aurata Exposed to Waterborne Cadmium - T. Cirillo; R. Amodio Cocchieri; E. Fasano; A. Lucisano; S. Tafuri; M. C. Ferrante; E. Carpenè; G. Andreani; G. Isani (Archives of Environmental Contamination and Toxicology, 2012)

Passive and active shaping of unitary responses from associational/commissural and perforant path synapses in hippocampal CA3 pyramidal cells - Tamara Perez-Rosello; John L. Baker; Michele Ferrante; Satish Iyengar; Giorgio A. Ascoli; Germán Barrionuevo (Journal of Computational Neuroscience, 2011)

Regional surveillance of emergency-department visits for outpatient adverse drug events - A. Capuano; A. Irpino; M. Gallo; L. Ferrante; M. L. Illiano; B. Rinaldi; A. Filippelli; F. Rossi (European Journal of Clinical Pharmacology, 2009)

Persistent Organochlorine Pollutants in Liver of Birds of Different Trophic Levels from Coastal Areas of Campania, Italy - B. Naso; D. Perrone; M. C. Ferrante; A. Zaccaroni; A. Lucisano (Archives of Environmental Contamination and Toxicology, 2003)

The water-soluble components of the essential oil of Melaleuca alternifolia (tea tree oil) suppress the production of superoxide by human monocytes, but not neutrophils, activated in vitro - C. Brand; A. Ferrante; R.H. Prager; T.V. Riley; C.F. Carson; J.J. Finlay-Jones; P.H. Hart (Inflammation Research, 2001)

Rapid degradation of articular cartilage proteoglycan by neutrophils: Comparison with macrophages and synovial fibroblasts - D.A. Halliday; G. Clemente; D.A. Rathjen; A. Ferrante (Inflammation Research, 2000)

Polymorphic genotypes of the HRES-1 human endogenous retrovirus locus correlate with systemic lupus erythematosus and autoreactivity - Claudio Magistrelli; Ella Samoilova; Rajeev K. Agarwal; Katalin Banki; Pasquale Ferrante; Adrian Vladutiu; Paul E. Phillips; A. Perl (Immunogenetics, 1999)

Subgrouping of human rotavirus strains by complement fixation, indirect double-antibody sandwich enzyme-linked immunosorbent assay and solid-phase immune electron microscopy - G. Gerna; M. Torsellini; N. Passarani; M. Battaglia; E. Percivalle; A. Sarasini; D. Torre; P. Ferrante (Archives of Virology, 1984)